KONTRIBUSI MAJELIS ULAMA INDONESIA PROVINSI JAWA TIMUR DALAM MENUMBUHKEMBANGKAN INDUSTRI HALAL - Ubaidillah, M Hasan; Ningtyas, Mega Ayu (LPPM Sekolah Tinggi Ilmu Al-Qur'an Wali Songo Situbondo, 2025)
The enactment of Law of the Republic of Indonesia Number 33 of 2014 concerning Halal Product Assurance, so that the submission of halal certification by producers is mandatory. The provisions regarding the obligation of halal certification for all products are stated in Article 4 which states that: